Bacterial flora in frozen semen of Murrah buffalo bulls and their antibiogram - SINGH, M P; PRASAD, J K; SAXENA, M S; KUMARI, PRATIMA (The Indian Journal of Animal Reproduction, 2023)
A total of 28 frozen semen samples were screened for bacteria and 29 bacterial isolates were obtained. Out of29 isolated bacteria, 6 were identified as Staphylococcus aureus (20.68%), 4 as Bacillus sp. (13.79%), 4 as Escherichia coli (13.790/o), 4 as Alcaligenes faecalis (13.79%), 4 as Proteus sp. (13.79%), 4 as Citrobacter sp. (13.790/o) and 3 as Pseudomonas aeruginosa (10,34%). Antibiotic sensitivity test was performed against 12 different antibiotic discs (Amikadn, enrofloxacin, gentamicin, chloramphenicol, ciprofloxacin, cephalexin, streptomycin, amoxycillin, ampicillin, erythromycin, norfloxacin and penicillin). The results of sensitivity test revealed that gram positive bacteria were more .susceptible as compared to gram negative bacteria with antimicrobials used in the study. Bacillus sp. and Alcaligenes faeca/is were found to be susceptible to all the antimicrobials used, whereas Pseuodomonas aeruginosa was sensitive to ciprofloxacin, gentamicin, amikacin and enrofloxacin only. Amikacin and ciprofloxacin were found to be most effective (89.65%) against the isolates, followed by enrofloxacin (86.20%), genatamicin (82.75%), norfloxacin (79.31%), chloramphenicol (72.41%), cephalexin (68.97%) ampicillin (48.27%), streptomycin (44.82%) penicillin (37.93%), amoxycillin (31.03%) and erythromycin (20.68%).